Effect of Different Operational Parameters on Bio-degradation of Chicken Feathers by Aspergillus niger: Investigation Under Submerged Fermentation Process: Parameters on Bio-degradation of Chicken Feathers - Javeed, Faisal; Shahid, Memuna Ghafoor; Javed, Ali (Biological Sciences - PJSIR, 2020)
Fungal strain, Aspergillus niger (ATCC 1015) has ability to grow on keratinous material therefore, it was selected for the investigating bio-degradation of chicken feathers. Different operational parameters were studied under submerged fermentation process i.e. effect of substrate concentration, effect of pH, effect of incubation temperature, effect of yeast extract concentration and effect of volume of fermentation medium. A. niger was grown on solid medium of malt extract and agar, due to its ability of rapid growth on it. Complete bio-degradation of the substrate was achieved after 5 days (0.70±0.03 U/mL) under standard optimized conditions. Investigation of different operational parameters on bio-degradation of chicken feathers revealed, maximum keratinolytic was observed at 40 °C incubation temperature, at 0.5 g/100 mL of substrate concentration, 8 g/100 mL concentration of yeast extract, at 7 pH of the fermentation medium and at 50 mL volume of fermentation medium. The present study suggests that A. niger could prove to be a potential candidate for production of keratinase and bio-degradation of chicken feathers.